2009
DOI: 10.1111/j.1525-1403.2009.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Stimulation: A Treatment for Chronic Low Back Pain and Failed Back Surgery Syndrome?

Abstract: Objective. This study aims to evaluate the usefulness of peripheral nerve stimulation as a treatment option for patients with chronic low back pain. Materials and Methods. More than 12 months, we collected data on consecutive patients who had successful trials and were subsequently implanted with octrode percutaneous leads placed subcutaneously within the major area of pain. Eleven patients met diagnostic criteria for failed back surgery syndrome. A questionnaire assessed outcomes including: pain, analgesic us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 40 publications
(69 reference statements)
1
34
0
Order By: Relevance
“…Currently, these patients may be less suitable for SCS due to lower response rates over time (11)(12)(13). Case reports regarding the use of subcutaneous stimulation alone or as add on therapy to SCS in treating low back pain reported positive outcomes (14)(15)(16)(17)(18). A feasibility study performed by our group (15) showed a statistically significant reduction of pain in the leg and the lower back after 12 months of treatment with subcutaneous stimulation as add-on therapy to spinal cord stimulation in FBSS patients.…”
Section: Introductionmentioning
confidence: 86%
“…Currently, these patients may be less suitable for SCS due to lower response rates over time (11)(12)(13). Case reports regarding the use of subcutaneous stimulation alone or as add on therapy to SCS in treating low back pain reported positive outcomes (14)(15)(16)(17)(18). A feasibility study performed by our group (15) showed a statistically significant reduction of pain in the leg and the lower back after 12 months of treatment with subcutaneous stimulation as add-on therapy to spinal cord stimulation in FBSS patients.…”
Section: Introductionmentioning
confidence: 86%
“…The mechanisms are likely similar to those of SCS . Verrills et al . demonstrated that peripheral nerve stimulation provided an average pain reduction in 3.77 visual analog points in patients with FBSS at an average follow‐up time of 7 months.…”
Section: Management Of Fbssmentioning
confidence: 99%
“…Paicius et al [4] first reported a series of 6 patients, 5 of whom had prior lumbar surgery with all patients noting greater than 50% pain relief. Verrills et al [18] reported that among 13 consecutively implanted patients 85% noted greater than 50% pain relief with a mean follow-up period of 7 months. Although long-term data are not available, Krutsch et al [19] reported a single patient with lumbar FBSS who had 90% improvement at 12 months postimplant.…”
Section: Failed Back Surgery Syndromementioning
confidence: 98%